The Effect of Propranolol and Midazolam on the Reconsolidation of a Morphine Place Preference in Chronically Treated Rats - Robinson, Michael J.; Armson, Michael; Franklin, Keith B. (Frontiers in Behavioral Neuroscience, 2011)
A stable memory can be disrupted if amnestic treatment is applied in conjunction with memory reactivation. Recent findings in the conditioned place preference (CPP) model suggest that blocking reconsolidation attenuates the ability of environmental cues to induce craving and relapse in drug addicts, but the impact of prior physical dependence has not been described. We examined the effect of post-reactivation amnestic treatment on reconsolidation of a CPP for morphine, in animals naïve to morphine, under chronic morphine experience or abstinent. Morphine experience was induced by escalating doses of morphine from 10 mg/kg/day (s.c.), and maintained on 30 mg/kg/day during the course of conditioning and reactivation procedures, or conditioning alone. Naïve and morphine-experienced animals were trained in a 3-compartment apparatus by 4 morphine (5 mg/kg, s.c.) and 4 saline experiences paired with either of two large conditioning compartments. The memory was then reactivated by a CPP test, and immediately afterwards animals received an injection of the beta-adrenergic antagonist propranolol (10 mg/kg, s.c.), the GABAa agonist midazolam (1 mg/kg, i.p.), or saline. Morphine-naïve rats received only a single reconsolidation blocking treatment (Exp 1), while chronic morphine rats were given 8 reactivation sessions each followed by amnestic treatment, either before (Exp 2) or after 10 days of withdrawal (Exp 3). Propranolol and midazolam disrupted reconsolidation in morphine- naïve rats, but failed to disrupt the CPP when rats were trained under chronic morphine treatment, even if they were recovered from chronic opiate exposure before reactivation. In fact, propranolol increased the preference for the drug-paired context in animals trained while maintained on chronic morphine. Midazolam had little effect. Morphine experience may produce neurochemical changes which alter memory storage processes and reduce the impact of amnestic treatments on reconsolidation.